Jaminan Hukum bagi Pecandu Narkotika sebagai Korban Penyalahgunaan Narkotika di Indonesia: Studi Yuridis Normatif terhadap Putusan Nomor 2291/Pid.Sus/2025/PN Mdn - Effnavel Legislatif Mission Lubis; Zico Ricardo Aritonang (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Narcotics abuse remains a serious legal and social problem in Indonesia. Although Law Number 35 of 2009 concerning Narcotics has provided for rehabilitation measures for narcotics addicts and victims of narcotics abuse, its implementation has not always been carried out optimally. This study aims to analyze the legal framework governing the protection guarantees afforded to narcotics addicts as victims of narcotics abuse, its application in Decision Number 2291/Pid.Sus/2025/PN Mdn, and its assessment from the perspectives of legal protection theory, modern sentencing theory, and victimology. The research employs a normative juridical method using statutory, case, and conceptual approaches. The findings reveal that the Indonesian legal system has established legal protection through medical rehabilitation and social rehabilitation as principal mechanisms for the recovery of narcotics addicts. An analysis of Decision Number 2291/Pid.Sus/2025/PN Mdn demonstrates that the defendant was more appropriately classified as a narcotics user or addict rather than a participant in illicit narcotics trafficking, thereby rendering a rehabilitative approach more appropriate than imprisonment. The application of rehabilitation in the decision reflects consistency between statutory provisions and judicial practice oriented toward recovery and social reintegration. The novelty of this study lies in its analysis of Decision Number 2291/Pid.Sus/2025/PN Mdn through the integrated application of legal protection theory, modern sentencing theory, and victimological perspectives to reinforce the legal status of narcotics addicts as victims of narcotics abuse and to strengthen a more humane and recovery-oriented approach within Indonesia’s narcotics law enforcement system.